Analysis of financial statements on NYUCI LOUNDRY MSMEs based on financial accounting standards (SAK-EMKM) - Sri Liniarti; Rizky Surya Andhayani Nasution; Yunanda Eka Putra; Farida Khairani Lubis; Elina R Gustarina (Indonesia Accounting Research Journal, 2025)
This research aims to find out the financial statements of MSMEs Loundry NYCUI based on SAK EMKM and identify financial reporting obstacles experienced by MSMEs Loundry NYUCI based on SAK EMKM. This research uses a descriptive qualitative method, using primary and secondary data. The data collection technique used is interviews. The results of this study confirm that the financial statements of NYUCI Loundry do not meet the requirements of SAK EMKM. The problems experienced by Loundry NYUCI in financial reporting based on EMKM SAK are caused by a ignorance of EMKM SAK, ignorane of socialization of EMKM SAK, and ignorance of human resources in the field of accounting.